The Rosie effect [compact disc, unabridged] - Simsion, Graeme C. (Simon & Schuster Audio, 2014)
The Wife Project is complete, and Don and Rosie are happily married, living in New York. But they're about to face a new challenge because, surprise! Rosie is pregnant. Don sets about learning the protocols of becoming a father, but his unusual research style gets him into trouble with the law. As Don tries to schedule time for pregnancy research, getting friends Gene and Claudia to reconcile, and staying on the right side of the social worker, he might lose Rosie when she needs him the most.